Rancang Bangun Sistem Informasi Penerimaan dan Pengeluaran Kas di STMIK Antar Bangsa - Nurbaiti (Jurnal Sistem Informasi, 2019)
Abstract— The cash receipt and expenditure system used in STMIK Antar Bangsa has been computerized but still uses Microsoft Excel and has not been integrated with the database, causing some obstacles such as requiring a long time to prepare financial statements so that a system that can be used as a reference to help performance is needed financial department. By using the cash information system acceptance and expenditure application is expected to help the work of the finance department, especially in making financial statements.